Characterization of a novel POLD1 missense founder mutation in a Spanish population. (April 2017) - Ferrer‐Avargues, Rosario; Díez‐Obrero, Virginia; Martín‐Tomás, Ester; Hernández‐Illán, Eva; Castillejo, María‐Isabel; Codoñer‐Alejos, Alan; Barberá, Víctor‐Manuel; Sánchez‐Heras, Ana‐Beatriz; Segura, Ángel; Juan, María‐José; Tena, Isabel; Castillejo, Adela; et al.
Abstract: Background: We identified a new and a recurrent POLD1 mutation associated with predisposition to colorectal cancer (CRC). We characterized the molecular and clinical nature of the potential POLD1 founder mutation in families from Valencia (Spain). Methods: Clinical and molecular data were collected from four independent families known to have a POLD1 Leu474Pro mutation. To establish its founder effect, haplotype construction was performed using 14 flanking POLD1 polymorphic markers. We calculated penetrance estimates and clinical expressivity, globally and stratified by age and sex. Results: We included 32 individuals from the four families: 20 carriers and 12 noncarriers. A common haplotype was identified in these families in a region comprising 2, 995 Mb, confirming L474P as the first founder POLD1 mutation identified. Thirteen tumors diagnosed in 10 POLD1 carriers: eight CRC, three endometrial and two other tumors were considered. The median age of cancer onset for POLD1 mutation carriers was 48 years. The observed penetrance was 50% and the cumulative risk at age of 50 years was 30%. Conclusions: The findings of the present study contribute to a better understanding of CRC genetics in the Spanish population. The clinical phenotype for this mutation is similar to that in Lynch syndrome. Future studies using next generation sequencing with large gene panels for any hereditary cancer condition will offer the possibility of detecting POLE/POLD1 mutations in unsuspected clinical situations, demonstrating a more real and unbiased picture of the associated phenotype.